Augustan Allusion: Quotation and Self-Quotation in Pope's Odyssey. (9th January 2019) - Calvert, Ian
Abstract: The status of Pope's Homer as a text which engages with numerous seventeenth-century poems and translations of classical epics is well established. Much of the criticism on this topic has so far focused on Pope's use of Paradise Lost and Dryden's Works of Virgil . This article contends that Pope's use of other writers in the translation, including Denham and Waller, has been under-appreciated. I examine some previously unacknowledged borrowings from Denham and Waller in Pope's Odyssey and relate them to Pope's use of Milton and Dryden. I suggest that, within the context of direct quotation of whole verse-lines, Pope was himself responsible for privileging the presence of certain seventeenth-century authors in his Homer translations over others. The quotations of complete lines from Milton and Dryden are designed as 'outward-looking', but those from Denham and Waller are more 'inward-looking' and represent moments where he is reflecting privately on the main characteristics of their allusive strategies. Pope acknowledges that where Denham's primary intertextual relationship was with Waller, the key source for Waller himself was his own early poetry. Waller's early poems had, in turn, frequently drawn on works by other poets, and I outline how, in his Homer translations, Pope too repeats certain quotations frequently enough that they begin to function as self-quotations. I subsequently connect this technique to Pope's readiness to repeat lines across his Iliad and Odyssey that are (largely) of his own invention to suggest that, in general, Pope's allusive poetics follow Waller's intertextual practice more closely than those of his other antecedents.